Development and effectiveness of i-ProMaths module on achievement, thinking skills, motivation and engagement in calculus among matriculation students - Ramli, Mohd Shahridwan (2024)
Mathematical achievement is still seen as less than encouraging even though many investments have been made after comparisons at the global level have been made. At the matriculation level, it is not left behind when matriculation students’ mastery in calculus is seen as less impressive. In addition, through the needs analysis phase, matriculation students are seen to lack mastery of higher order thinking skills including critical and creative thinking skills. Likewise, from the aspect of motivation and student engagement that still needs attention. Therefore, a module was developed using the flipped classroom and problem-based learning (PBL) to help improve understanding in calculus at the matriculation level. The module called i-ProMaths module was developed based on the ADDIE (analyse, develop, design, implement, evaluate) model. During the needs analysis phase, semi-structured interviews were conducted together with six experienced senior lecturers from various matriculation colleges. The i-ProMaths module received validation from seven expert panels. Besides, the i-ProMaths module has also received high validity and reliability values, exceeding the coefficient value of 0.90. The effectiveness of the i-ProMaths module was tested using a quasi-experimental design with a pre-post test conducted at one of the matriculation colleges in Kelantan. A total of 98 respondents consisting of four tutorial groups were involved in this study and divided into four different groups consisting of three experimental groups using the i-ProMaths module (flipped classroom and PBL), the ProMaths module (PBL), the i-Maths module (flipped classroom) and a control group using the module ConventMaths (conventional). The findings of the study show that students who were exposed to the i-ProMaths module significantly had better achievement in the post-test and delayed post-test compared to the other groups followed by the ProMaths, i-Maths and lastly ConventMaths groups. In addition, students in the i-ProMaths group significantly showed a better level of critical and creative thinking skills compared to other groups. Meanwhile, the results of motivation scores and student engagement also show significant differences in the i-ProMaths group compared to other groups. This study gives the implication that learning calculus integrated by flipped classroom and PBL module can help students gain achievement, critical and creative thinking skills, better motivation, and student engagement. In other words, the use of flipped classroom and PBL is suitable to be used in the teaching and learning of calculus to introduce the concept of calculus more clearly.